Pembuatan Katrol Sebagai Alat Peraga Berbasis Mekanikal di SMA Sekolah Rakyat Bekasi - Adhes Gamayel; Ade Sunardi (Universitas Mathla'ul Anwar Banten, 2017)
PULLEY PRODUCTION AS A MECHANICAL-BASED PROPS IN SMA SEKOLAH RAKYAT OF BEKASI. Pulley is a simple lift aircraft that enter the high school physics lesson. But the student of SMA Sekolah Rakyat (SR) Bekasi lack of understanding of the concept of the pulley so that did not like this subject. To overcome this issue, props with basic of mechanical where pulleys arrange on single and multilevel had been made. Activity methods are manufacture, trials the props, demontration and handover the props, processing data between pretest and posttest. Result show that student do the post test with good score after trial the props. Pulley props facilitate student of SMA SR Bekasi to better understand the concept of a simple lift aircraft.